Impact of capital structure on operational efficiency - Evidence from Vietnam - Do, Phuong Huyen (Tạp chí Công thương, 2020)
The paper is a contribution to knowledge in the field of corporate finance by way of investigating the impact of capital structure on the performance and efficiency of join stock listed companies in Vietnam. The results confirm that there exists a trongly significant positive correlation between dedt-to-equity ratio and operational efficiency of the sample.